2022
DOI: 10.3390/molecules27041228
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Phytochemical Characteristics of Different Parts of Hypericum scabrum L. Extracts, Essential Oils, and Their Antimicrobial Potential

Abstract: Hypericum (Hypericaceae) is a genus that comprises a high number of species around the world. In this study, the roots, aerial parts, flowers, fruits, and aerial parts with flowers from Hypericum scabrum were macerated separately by methanol and water and then fractionated by different solvents of, such as ethyl acetate, n-hexane, butanol, dichloromethane, aqueous residue sub-extracts, and ethnobotanical use. All the extracts, sub-extracts and essential oils of H. scabrum were investigated for the first time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…H. empetrifolium, which presented greater activity, yielded higher amounts of monoterpene hydrocarbons (especially α-pinene) in comparison with the other under-investigation species [39]. H. scabrum EO obtained from flowers was found active against the same strain of C. tropicalis (ATCC 750) with an MIC value of 312.5 µg/mL, while the MIC value from the EO from aerial parts was 156.25 µg/mL, which could be explained by the differences in the levels of α-pinene in the biomass used (55.6% in flowers vs. 17.5% in aerial parts) [70]. Antimicrobial effects of Hypericum EOs against C. krusei were firstly evaluated during the last decade, for a clinical isolate as mentioned above [39], as well as the strain ATCC 6258 for H. triquertifolium EOs [72] and H. scabrum [69], which showed selective antimicrobial activity with IC 50 104.43 µg/mL (amphotericin B used as positive control showed IC 50 0.52 µg/mL).…”
Section: Antifungal Activitymentioning
confidence: 97%
See 2 more Smart Citations
“…H. empetrifolium, which presented greater activity, yielded higher amounts of monoterpene hydrocarbons (especially α-pinene) in comparison with the other under-investigation species [39]. H. scabrum EO obtained from flowers was found active against the same strain of C. tropicalis (ATCC 750) with an MIC value of 312.5 µg/mL, while the MIC value from the EO from aerial parts was 156.25 µg/mL, which could be explained by the differences in the levels of α-pinene in the biomass used (55.6% in flowers vs. 17.5% in aerial parts) [70]. Antimicrobial effects of Hypericum EOs against C. krusei were firstly evaluated during the last decade, for a clinical isolate as mentioned above [39], as well as the strain ATCC 6258 for H. triquertifolium EOs [72] and H. scabrum [69], which showed selective antimicrobial activity with IC 50 104.43 µg/mL (amphotericin B used as positive control showed IC 50 0.52 µg/mL).…”
Section: Antifungal Activitymentioning
confidence: 97%
“…Contradictory results have been reported for Escherichia coli and Pseudomonas aureginosa, being either sensitive or resistant against the EOs from Hypericum spp. [24,32,39,41,64,70]. The observed differences could be attributed to experimental parameters such as the selected protocols, the tested concentrations, or the controls, as well as the chemical profile of the samples.…”
Section: In Vitro Studies Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical studies carried out on different Hypericum taxa have revealed the presence of bioactive specialized metabolites belonging to different classes, including phloroglucinols, napthodianthrones, flavonoids, phenylpropanes, essential oils (EOs), benzophenones, and xanthones [ 9 , 10 ]. Most compounds show a wide range of biological properties, such as antimicrobial [ 11 , 12 , 13 ], anti-inflammatory [ 14 ], anticholinesterase [ 15 , 16 ], anti-cancer [ 17 , 18 ], antioxidant [ 19 , 20 ], anticholinesterase [ 20 ], hypoglycemic [ 21 ], anti-collagenase and anti-elastase [ 22 ], immunosuppressive [ 23 , 24 ], and immunomodulatory effects [ 25 ]. For example, the naphthodianthrones hypericin and pseudohypericin, the prenylated phloroglucinol hyperforin, and the flavonoid amentofavone are considered the main compounds responsible for the antidepressant activity of H. perforatum [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The flowers (30 g), roots (60 g), leaves (31 g) and aerial parts (90 g) of TS were placed separately in balloons connected to a Clevenger appliance, water was annexed to them, and essential oils were gained after about 3–4 h. The compositions of essential oils were analysed by GC‐FID and GC–MS methods. The details of GC‐FID and GC–MS methods of essential oils were given in the method of the study by Ergin et al 11 The GC–MS analysis was carried out with an Agilent 5975 GC–MSD system. Innowax FSC column (60 m × 0.25 mm, 0.25 μm film thickness) was used with helium (high purity) as carrier gas (0.8 mL/min).…”
Section: Methodsmentioning
confidence: 99%